Створення стратегій тестування для оптимального поєднання ручного та автоматизованого тестування в стартап-проектах - Mokrytska, O. V.; Trukhan, D. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
The paper considers the creation of a testing strategy for a startup project that combines manual and automated testing. Automation is implemented using the AirTest IDE and the Python programming language. Particular attention is paid to the choice of tools to ensure high test coverage of the main project functions. Manual testing is used for more complex scenarios, while automation covers routine tasks. The strategy is aimed at improving the quality of the product with minimal resource consumption.